Pengembangan Media Interactive Assisted Learning (IVAL) dalam Mata Kuliah Asesmen untuk Mahasiswa Tunagrahita Ringan - Badroeni -; Erik Wahyudin; Sofhian Fajrin Nasrulloh; Rela Imanulhaq (FKOM UNIKU, 2024)
The development of an innovative interactive assisted learning (IVAL) model for mildly mentally retarded students is an effort to create solutions related to the need for digital-based media to stimulate mildly mentally retarded students in assisting the learning process, in this context, in early childhood learning assessment courses at the PG-PAUD STKIP Muhammadiyah Kuningan. In fact, it has not used digital media to help students with special needs due to limited innovation of digital-based media. Through the research and development process carried out, the results of this research creates an android application entitled